At the 'risky' end of things: labelling, self-concept and the role of supportive relationships in young lives. (16th March 2023) - Matos, Raquel; Campos, Luísa; Martins, Filipe; Deakin, Jo; Carneiro, Alexandra; Fox, Claire; Markina, Anna
ABSTRACT: The 'risky' label attached to certain groups of young people has disproportionately made them the target of 'interventions' designed to monitor, rehabilitate or punish. This article explores how young people experience and respond to that label across many aspects of their lives from school to leisure and from justice to welfare. We employ the notion of self-concept to understand the negative impact of labelling on young people and by contrast, the enabling influence of supportive relationships. Our analysis points to a relevant link between labelling and conflict and young people's self-concept, as well as to the relationship between self-concept and demonstrations of different forms of agency. Drawing on key findings from a meta-ethnographic synthesis of case studies from three countries (Estonia, Portugal and UK), we find that, regardless of the country where young people live, the significant relationships in their lives are essential for breaking the 'risk-labelled' cycle and to promote a more positive path. The case studies were developed with 71 participants (49 male), mostly aged between 15 and 24 years old, who presented long paths of conflict with major normative social institutions like the family, school, or the law, frequently leading to school exclusion and, sometimes, anti-social or criminal behaviour.